2022
DOI: 10.1039/d2sc02222b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing CO2 electroreduction to CH4 over Cu nanoparticles supported on N-doped carbon

Abstract: The pyrrolic N in Cu-np/NC composites can enhance the activation of H2O, resulting in excellent selectivity for CH4 and high current density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…CH 4 is more difficult to produce via CO 2 R compared to the other C1 products due to the high C-H bond energy (434 kJ mol −1 ) and the 8e − -transfer demand. 33,40,[89][90][91][92][93] Therefore, it is a challenge to achieve high FE and current density. To the best of our knowledge, only three articles have reported satisfactory FE and current density in the IL-based electrolytes, as summarized in Fig.…”
Section: Ch 4 As the Target Productmentioning
confidence: 99%
“…CH 4 is more difficult to produce via CO 2 R compared to the other C1 products due to the high C-H bond energy (434 kJ mol −1 ) and the 8e − -transfer demand. 33,40,[89][90][91][92][93] Therefore, it is a challenge to achieve high FE and current density. To the best of our knowledge, only three articles have reported satisfactory FE and current density in the IL-based electrolytes, as summarized in Fig.…”
Section: Ch 4 As the Target Productmentioning
confidence: 99%
“…Based on the catalyst with Cu nanoparticles supported on N-doped carbon (Cu-np/NC), Han and co-workers clarified that the pyrrolic-N species in substrate promoted the *CO hydrogenation to *CHO intermediate, giving rise to enhanced CH 4 productivity. [87] Sargent and co-workers used the metal oxide cluster to modify Cu catalyst to increase the CH 4 formation. [88] The local *H availability on Cu surface was facilitated due to the modified metal oxide, which lowered the reaction barrier of CH 4 formation.…”
Section: Metal Heterointerfacesmentioning
confidence: 99%
“…CO 2 conversion to CH 4 on Cu catalysts has been extensively studied. While high CH 4 Faradaic efficiency (over 70%) at relatively high current density (over 200 mA cm –2 ) has been demonstrated, CO 2 -to-CH 4 stability is limited to tens of hours due to surface reconstruction. Much effort has been devoted to improving the stability for CH 4 production using pulse electrolysis. Jeon et al explored the symmetrical pulse CO 2 electroreduction reaction in a gas-fed flow cell, and they found that the CH 4 selectivity can be promoted when the anodic potential is over +1.0 V versus RHE ( E c = −0.7 V vs RHE), and the CH 4 FE could reach 48.3% as the anodic potential was increased to +1.2 V versus RHE compared to 0.1% at constant cathodic potential of −0.7 V versus RHE (Figure a).…”
Section: Pulse Electrolysis For Stable Ecrmentioning
confidence: 99%